A Cyber Security and Digital Transactions to Educated the Micro, Small and Medium Business Community - Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2023)
The rapid growth in the digital economy has brought countless benefits, especially in the micro, small, and medium enterprise (MSME) community. However, along with these opportunities, serious threats also emerge in the form of increasingly sophisticated cybercrime. This article aims to explain the important role of cyber security in digital transactions and how it can be used as an educational tool for the MSME community. The importance of understanding cyber threats and cyber security practices in a rapidly changing digital era cannot be underestimated. This article discusses the various types of cyber threats that MSMEs may face, such as phishing, malware, and ransomware attacks, as well as the financial and reputational impact these attacks can have. Additionally, this article highlights the cyber security principles that MSMEs must follow to protect their data and digital transactions. Apart from explaining threats, this article also promotes the role of education in increasing MSME awareness and understanding of cyber security. We present practical recommendations on how MSMEs can educate themselves and their team members on cybersecurity best practices. Additionally, this article discusses available resources, such as online training and security tools that can help MSMEs protect their businesses from cyber threats. With a better understanding of cyber security and best practices in digital transactions, the MSME community can reduce the risk of data and financial loss, and build a stronger foundation for sustainable growth in the digital economy era. This article provides useful guidance for the MSME community looking to strengthen their defenses against cyber threats and harness the unlimited potential of secure digital transactions.